IEP-2005 : writing and implementing individualized education programs (IEPs) - Burns, Edward, 1943- (Charles C Thomas Publisher, 2006)
The purpose of this book is to provide guidelines to develop appropriate Individualized Education Programs (IEPs) for children with disabilities based on the Individuals with Disabilities Education Act amendments of 2004 (IDEA-2004) or Public Law 108-446. These guidelines are intended to result in IEPs that are streamlined, focused, and reasonably calculated to provide educational benefit. Specifically, this work is directed toward developing IEPs that provide every child with a free and appropriate public education, rather than to develop IEPs that merely show compliance with IDEA but confuse.